삼척지역 성인 및 노인 남녀의 연령별 식행동과 식사의 질 평가 - 김미현(Mi Hyun Kim); 이재철(Jae Cheol Lee); 배윤정(Yun Jung Bae) (Korean journal of community nutrition, 2009)
The purpose of this study was to evaluate the eating behaviors and dietary quality of various aged adults. This study conducted through questionnaire and dietary survey by 24-hr recall to 850 adults residing in Samcheok. Subjects were divided into four groups according to the age in male and female, which included 20~29 yrs group (male n = 94, female n = 66), 30~49 yrs group (male n = 201, female n = 216), 50~64 yrs group (male n = 88, female n = 96), and $≥65$ yrs group (n = 46, female n = 43). In male, 20~29 yrs group had a larger proportion of subjects who skipped breakfast, lunch and dinner compared to other groups (p < 0.001, p < 0.05, p < 0.01). The daily food and energy intakes in $≥50$ yrs group were significantly lower than those of < 50 yrs. Protein and fat intakes of 20~29 yrs group were significantly higher than those of the other groups. But ND (Nutrient Density) of minerals as like calcium, iron and plant iron in 20~29 yrs group were significantly lower than those of other groups. The KDDS (Korean's Dietary Diversity Score) of 20~29 yrs group, 30~49 yrs group, 50~64 yrs group and $≥65$ yrs group in male were 4.1, 3.8, 3.7 and 3.5 respectively and there was significant difference (p < 0.001). In female, skipping breakfast and dinner were significantly higher in 20~29 yrs group than in other groups (p < 0.001, p < 0.001). And the use of nutrient supplementation was higher in 30~49 yrs group than that of other groups (p < 0.05). The daily energy intakes was higher in 20~49 yrs group than that of $≥65$ yrs group. The ND (Nutrient Density) of animal protein, vitamins A and $B_1$ in 20~29 yrs group were significantly lower than those of other groups. The KDDS of 20~29 yrs group, 30~49 yrs group, 50~64 yrs group and $≥65$ yrs group in female were 4.0, 3.9, 3.9 and 3.6 respectively and $≥65$ yrs group was significant lower than other groups. According to these results, $≥65$ yrs and 20~29 yrs group had more dietary habit problems and poor nutrition status than 30~64 yrs group. The results of this study revealed that nutritional management and education for adequate meals should be emphasized in adults and elderly.